2009
DOI: 10.1007/s11664-008-0641-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, and Transport Properties of Na22Si136

Abstract: The type II clathrate Na 22 Si 136 is prepared by the thermal decomposition of NaSi. Thermal analysis indicates this phase is metastable yet has a relatively high decomposition temperature. Rietveld analysis indicates that Na in the larger Si 28 cage is shifted off-center, analogous to observations in some type I clathrates. Temperature-dependent electrical and thermal transport properties are reported for Na 22 Si 136 , for which the spark plasma sintering technique was found to be effective in achieving inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
2
17
1
Order By: Relevance
“…A previous study concluded that NMR results are consistent with either the Na atoms in a static position at the center of the Si 28 cage, or the Na are dynamically disordered but symmetric about the center of the Si 28 cage ͑but not statically disordered off center͒. 31 Our XANES results and also our powder XRD refinements 44 both indicate displacements of the Na in the Si 28 cages of 0.5 Å, uncertain to within Ϯ0.1 Å. Therefore, taking this together with the NMR results, 31 we can conclude that Na is dynamically disordered in the Si 28 cages.…”
Section: Off-center Displacement Of Na In the Larger Cagessupporting
confidence: 80%
See 2 more Smart Citations
“…A previous study concluded that NMR results are consistent with either the Na atoms in a static position at the center of the Si 28 cage, or the Na are dynamically disordered but symmetric about the center of the Si 28 cage ͑but not statically disordered off center͒. 31 Our XANES results and also our powder XRD refinements 44 both indicate displacements of the Na in the Si 28 cages of 0.5 Å, uncertain to within Ϯ0.1 Å. Therefore, taking this together with the NMR results, 31 we can conclude that Na is dynamically disordered in the Si 28 cages.…”
Section: Off-center Displacement Of Na In the Larger Cagessupporting
confidence: 80%
“…Unfortunately, from the peak shapes and peak positions in the XANES simulations we were not able to confirm small changes in displacement with loading, as we see from the powder XRD refinement ͑ϳ0.4 Å at higher Na content to ϳ0.6 Å at lower Na content͒. 41,44 Therefore, the median offcenter displacement, 0.5 Å, was used for Na in the Si 28 cages in all further simulations. This displacement also was used for the Na in the Si 28 cages in the EXAFS spectra discussed above.…”
Section: Off-center Displacement Of Na In the Larger Cagesmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast to majority of clathrate types, where semiconducting properties are hardly violated, in the case of type-II clathrates, metallic behavior is more norm than exception. Most of type-II clathrates feature frameworks made of single kind of atoms, Na 24−x Si 136 being a typical example [19]. In these clathrates, the strength of Si-Si bond (226 kJ/mol) outplays energy loss Thermoelectric Power Generation by Clathrates http://dx.doi.org/10.5772/65600 associated with illing the botom of conduction band by electrons upon occupation of the guest sites by sodium.…”
Section: Application Of Zintl Scheme and Electronic Structuresmentioning
confidence: 99%
“…There are rare cases of pure metallic properties, where electrical conductivity decreases with temperature as for Na 22 Si 136 [19] Type-II clathrates are diferent from those of other types in displaying metallic type of electrical conductivity, and many of them behave as normal metals. In particular, Cs 8 Na 16 Si 136 and Cs 8 Na 16 Ge 136 combine high electrical conductivity manifested by smooth increase in electrical resistivity with temperature-independent Pauli paramagnetism; such combination is typical for good metals [38].…”
Section: Sample Densiicationmentioning
confidence: 99%